L’étude préalable et la conservation - restauration des graffitis des internés au camp de Drancy - Mélanie Curdy (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
During the Second World War, the Jewish prisoners of the transit camp in Drancy inscribed messages on the walls of their prison. Concealed under coats of whitewash and plasters, the graffiti have been preserved on the walls of the former camp that has been turned into apartments again. The preliminary study of the graffiti were conducted at the Institut national du patrimoine. A scientific study led to the implementation of non-invasive examination methods of the covered mural inscriptions through the testing of potential applications of terahertz imaging. The graffiti were then conserved in order to ensure their legibility and preservation.